1996
DOI: 10.1111/j.1432-1033.1996.0173h.x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Analysis and Inactivation of the ndhK Gene Encoding a Subunit of NADH Quinone Oxidoreductase from Anabaena PCC 7120

Abstract: The function of the type-I pyridine nucleotide dehydrogenase (NDH-1) in the cyanobacterium Anabaena PCC 7120 was investigated. Immunological analysis with antibodies raised against NdhK from Synechocystis PCC 6803, a subunit of NDH-1, showed that NdhK in Anabaena PCC 7120 is only present on the plasma membrane, which confirms the results of previous studies [Howitt, C. A., Smith, G. D. & Day, D. A. (1993) Biochim. Biophys. Acta 1141, 313-3201. Southern analysis with probes from the operon encoding ndhC-K-J fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Therefore, a second ndhK gene exists in this species, but its activation seems to depend on growth conditions prevailing during inactivation of the chromosomal ndhK gene. Nevertheless, the existence of a cryptic homolog of ndhK suggests that the NdhK product is important in Synechocystis as in Anabaena [13]. Some ndh genes have been previously reported to be essential to the growth of other cyanobacterial species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a second ndhK gene exists in this species, but its activation seems to depend on growth conditions prevailing during inactivation of the chromosomal ndhK gene. Nevertheless, the existence of a cryptic homolog of ndhK suggests that the NdhK product is important in Synechocystis as in Anabaena [13]. Some ndh genes have been previously reported to be essential to the growth of other cyanobacterial species.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the differential expression of multicopy ndh genes and on the existence of contrasted phenotypes of inactivated mutants, the existence of different Ndh‐1 complexes with different functionalities and subunit compositions was proposed [8–12]. In other cyanobacterial species, like Plectonema boryanum or Anabaena PCC7120, attempts to inactivate ndhA , I , G or E and ndhK , respectively, have been unsuccessful, thus suggesting that these genes are essential in these cyanobacterial species (Y. Takahashi, unpublished data, [13]). However, until now, no reports have concluded that any of the ndh genes is essential to the survival of Synechocystis PCC6803.…”
Section: Introductionmentioning
confidence: 99%
“…Stops codons that are in frame with the first potential initiation codon in pea and lupin are written in lower case. morpha (Ohyama et al 1986), Synechocystis (Steinmiiller et al 1989) and Anabaena (Howitt et al 1996) reveals that overall amino acid sequence identities range from 63 to 86%. This homology is still at 45-50% if sequences of the NdhK homologues from mitochondria and eubacteria are included.…”
Section: Resultsmentioning
confidence: 99%
“…These findings suggest that for most of the chloroplast ndhK genes sequenced so far, the initiation codon may have been wrongly assigned about 22 codons upstream of the true one giving rise to the overlap of ndhC and ndhK genes, although this should be confirmed by N-terminal sequencing of their products. Nevertheless, the two cyanobacterial ndhK genes studied are 15-19 amino acids longer in its N-terminal end (Steinmuller et al 1989, Howitt et al 1996, causing a partial overlap of ndhC and ndhK in Anabaena (Howitt et al 1996).…”
Section: Resultsmentioning
confidence: 99%
“…PCC7120 [26] and keeping in mind the evolutionary proximity of Anabaena sp. PCC7120 to plant chloroplast genomes than to Synechocystis [16,37] the protocol of Hall et al [1] originally developed for preparation of stroma, thylakoid membrane, and lumen fractions from Arabidopsis thaliana chloroplasts was modified and used in the present study.…”
Section: Introductionmentioning
confidence: 99%